UEDGE modelling of detached divertor operation for long‐leg divertor geometries in ARC. Issue 6 (2nd March 2018) - Wigram, M.; LaBombard, B.; Umansky, M.V.; Kuang, A.Q.; Brunner, D.; Terry, J.L.; Golfinopoulos, T.; Rensink, M.E.; Whyte, D.G.
Abstract : Simulations of the ARC scrape‐off layer and divertor configuration are carried out using UEDGE to perform the first power‐handling assessment for the divertor design. A convective–diffusive anomalous transport model is implemented in the code to reproduce the radial plasma profiles anticipated for the device at the outer mid‐plane. Levels of exhaust power from the core are varied, and a 0.5% fixed fraction neon impurity seeding is included in investigations to find steady‐state detached solutions. Initial studies employing a super‐X divertor configuration have shown that a stable detached divertor‐operational window exists for reactor exhaust powers in the range of 72–92 MW, which is close to projected levels of exhaust power of 105 MW across the separatrix anticipated for ARC. Under these conditions, the divertor heat flux is fully dissipated by radiation and radial losses to the sidewalls of the divertor channel, leading to acceptable levels of power flux density on plasma‐facing components. Simulations are being extended to study the performance of the X‐point target geometry and to explore the sensitivity to the physics model and input parameters.